Peningkatan Kemampuan Berpikir Aljabar Sebagai Dampak Schema-Based Instruction - Farida, Anisatul; Farida; Andriani, Siska (Universitas Islam Negeri K.H. Abdurrahman Wahid Pekalongan, 2025)
This research aims to determine the effect of the model schema based instructution on students' algebraic thinking abilities on flat shape material at SMP Negeri Satu Atap 1 Way Tenong Lampung Barat. This research is a Quasy Experimental or pseudo-experimental research. The research design uses a Nonequivalent Control Group Design. This study uses two classes, namely the experimental class and the control class which are homogeneous in nature. The researcher implemented the target population and the accessible population. The target population is all students of SMP Negeri Satu Atap 1 Way Tenong, while the accessible population is all students of class VII of SMP Negeri Satu Atap 1 Way Tenong. In the sampling process, the researcher used the Cluster Random Sampling method. Data collection techniques used were tests, documentation, and observation. The hypothesis test used in this study is the t-test. Hypothesis test analysis results using independent t-test on algebraic thinking ability shows that the significance value is <0,05 so that H0 rejected and H1 accepted, which means learning Schema-Based Instruction influence the ability to think algebraically.